Effect of Falcaria vulgaris extracts on sperm parameters in diabetic rats. (2nd September 2018) - Jalili, Cyrus; Kamani, Mehran; Roshankhah, Shiva; Sadeghi, Hamid; Salahshoor, Mohammad Reza
Abstract: Diabetes causes a systemic inflammatory response with increased oxidative stress and can adversely effect spermatogenesis. Sickle‐weed plant, scientifically called Falcaria vlugaris, contains antioxidants and antimicrobial ingredients. The aim of this study was to determine the effect of Falcaria vulgaris vulgaris extract on the sperm parameters of diabetic rats. In this experimental study, diabetes was induced in the animals using streptozotocin (STZ; 60 mg/kg). Sixty‐four rats were equally divided into eight groups as follows: nondiabetic (normal) controls; normal rats given 50, 100 or 150 mg/kg doses of F. vulgaris extract; diabetic controls induced by STZ; and diabetic animals that received STZ plus 50, 100 or 150 mg/kg F. vulgaris extract. The animals were injected with the extract intraperitoneally once a day for 28 consecutive days. The sperm parameters of count, motility, morphology, viability, total antioxidant capacity and seminiferous tube diameter were analysed and compared. The results indicated that the values of all parameters decreased significantly in the diabetic control groups compared to the normal control group ( p < 0.00). The parameters of the diabetic groups that received 50, 100 or 150 mg/kg F. vulgaris extract showed significant increases in all parameters at all doses compared to the diabetic control group ( p ≤ 0.001). The administration of F. vulgaris extract as a potent antioxidant was able to compensate for the toxicity induced by STZ and increase the quality of some spermatozoa.